ANALISIS FITOLIT (PHYTOLITH ANALYSIS): PADA RESIDU ARTEFAK TULANG SITUS SONG BLENDRONG - Fajari, Nia Marniati Etie (Naditira Widya, 2009)
The result of phytolith analysis on Song Blendrong bone tools was the identification of a number of plant species which likely to had been benefited from by human in the past. In accordance to its morphological analysis, the identification was used as reference to interpret the function of Song Blendrong bone tools, which suggest their continuous use during the Pleistocene. It is futher suggested that humans in Song Blendrong used bone tools to exploit their surrounding enviroment, especially edible plant resources. This article discusses the phytolith analysis result that were done at bone tools from Song Blendrong rockshelter for describing the bone tools function.